Disposal of hazardous waste pesticides in Colorado - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes how to safely dispose of hazardous waste pesticides in Colorado.
CEPEP 01/03, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Hazardous wastes -- Colorado; Pesticides -- Waste disposal -- Colorado; Pesticides -- Environmental aspects -- Colorado